PENGEMBANGAN E-BOOK PADA MATERI SITUS SEJARAH PENINGGALAN HINDU-BUDHA DI KABUPATEN PASURUAN KELAS X UNTUK PEMBELAJARAN EKSKURSI - Muzaiyanah, Siti; Mustaji; Nurmida Catherine Sitompul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
E-book is one of the development media used for learning activities in the classroom. This is in accordance with current technological developments. During the development of technology, one of the learning resources in the form of physical books became less attractive. Low public access to reading power is an indicator identified in the Central Statistics Agency (BPS) survey based on the proportion of the population aged 10 years and over who access the media, especially when compared to the increase in public access to television. This is inversely proportional to public access to newspapers/magazines. The purpose of this research is to produce an e-book-based learning material in facilitating students as an interesting source of information with historical subject matter, especially regarding Hindu-Buddhist heritage in Pasuruan Regency, so as to increase the understanding of class X Senior High School students in teaching and learning activities in History subjects.